2014
DOI: 10.1128/aem.01015-14
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Sigma Factors SigF, SigE, and SigG Are Essential for Sporulation in Clostridium botulinum ATCC 3502

Abstract: Clostridium botulinum produces heat-resistant endospores that may germinate and outgrow into neurotoxic cultures in foods. Sporulation is regulated by the transcription factor Spo0A and the alternative sigma factors SigF, SigE, SigG, and SigK in most spore formers studied to date. We constructed mutants of sigF, sigE, and sigG in C. botulinum ATCC 3502 and used quantitative reverse transcriptase PCR and electron microscopy to assess their expression of the sporulation pathway on transcriptional and morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Recently, the sigF gene was disrupted in C. botulinum ATCC 3502 (96). As expected, the C. botulinum sigF disruption mutant was unable to form heat-resistant spores, and TEM image analysis revealed that sporulation was blocked at stage II (Fig.…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstsupporting
confidence: 61%
See 4 more Smart Citations
“…Recently, the sigF gene was disrupted in C. botulinum ATCC 3502 (96). As expected, the C. botulinum sigF disruption mutant was unable to form heat-resistant spores, and TEM image analysis revealed that sporulation was blocked at stage II (Fig.…”
Section: Sporulation-specific Sigma Factors That Are Activated Downstsupporting
confidence: 61%
“…The sigE gene was also disrupted in C. botulinum ATCC 3502 (96). This sigE mutant was unable to form viable heat-resistant spores, and TEM image analysis showed that sporulation was blocked at stage II, similar to the C. botulinum sigF disruption mutant (Fig.…”
Section: E the First Mother Cell-specific Sigma Factor Is Involvedmentioning
confidence: 83%
See 3 more Smart Citations